PROSEDUR PENCAIRAN DANA GANTI UANG PERSEDIAAN KAS BENDAHARA PENGELUARAN PADA DINAS PPKUKM DKI JAKARTA - Nadya Anggraini, (2023)
The purpose of this Final Project Report is to understand inventory reimbursement procedures in the workplace, as well as to fulfill the requirements for graduation from the Diploma Three program majoring in accounting at the Veteran National Development University Jakarta. The author conducted Field Work Practices (PKL) at the DKI Jakarta Industry Trade Cooperative Small and Medium Enterprises Office. Replenishment of inventory money that has been paid to the rightful party and submission of compensation for inventory money are routine activities carried out by the DKI Jakarta Department of Industry Trade Cooperatives Small and Medium Enterprises.